Pemberdayaan masyarakat melalui pengembangan wisata alam di Nagari Sitanang Kecamatan Ampek Nagari Kabupaten Agam Sumatera Barat - Thoyib NST, Abdullah Muhammad; Francisca, Sherlly Cindya (Departement Of Accounting, Indonesian Cooperative Institute, Indonesia, 2022)
This study aims to find out how the process of community empowerment through the development of natural tourism in Nagari Sitanang is carried out both from the problem analysis process and assessing regional potential, program planning, program implementation and the monitoring/supervision process. This research was conducted using a qualitative approach with a descriptive type of research. Primary data sources are Wali Nagari Sitanang, Nagari Sitanang apparatus, managers and communities involved in the empowerment process. Secondary data sources include data which are archives and documentation on community empowerment. The results of this study concluded that. First, the process of identifying potential areas and identifying problems is carried out using the PRA method. The potential possessed by Nagari Sitanang is the Batu Bagiriak Workshop. The problem found in Nagari Sitanang is the lack of community capacity in developing the Batu Bagiriak Workshop. Second, the program planning process, program planning using the FGD method and SOAR analysis, the results are increasing the capacity of the managers of the Batu Bagiriak Sarasah, mutual cooperation in cleaning the tourist sites of the Batu Bagirriak Sarasah, making stairs down, making changing rooms and building a prayer room. Third, the process of implementing the program, starting with outreach to the community, increasing the capacity of managers, making parking lots and making places to sell. Fourth, the monitoring process, the monitoring process is carried out periodically by holding meetings once a month.